Zimbabwe’s farmers struggle to feed the nation - Ish Mafundikwa (Africa Renewal, 2014)
Zimbabwe needs 1.8 million tonnes of the staple maize every year to meet the needs of its people and livestock. Only 798,500 tonnes were produced during the 2012/13 agricultural season. As a result, the country that was once dubbed “the breadbasket of the region” has to make up the deficit with imports and look to donors for food aid. After last year’s harvest, the World Food Programme, the UN food aid agency, forecast that an estimated 2.2 million people—equal to a quarter of the rural population— would need food assistance, from October 2013 through the early months of this year.